2011
DOI: 10.1007/s10236-011-0378-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the rheology and wave dissipation of kaolinite and natural Hendijan Coast mud, the Persian Gulf

Abstract: The objective of this paper is to investigate the rheological behavior of kaolinite and Hendijan mud, located at the northwest part of the Persian Gulf, and the dissipative role of this muddy bed on surface water waves. A series of laboratory rheological tests was conducted to investigate the rheological response of mud to rotary and cyclic shear rates. While a viscoplastic Bingham model can successfully be applied for continuous controlled shearstress tests, the rheology of fluid mud displays complex viscoela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…The model is used to study the effect of viscoelasticity on surface wave evolution. A comparison between the results of numerical wave model and the laboratory experiments of Soltanpour and Samsami (2011) confirms the accuracy of the numerical model. Figure (1) shows the variation of damping rate with surface wave frequency for various values of mud shear modulus.…”
Section: Resultssupporting
confidence: 64%
“…The model is used to study the effect of viscoelasticity on surface wave evolution. A comparison between the results of numerical wave model and the laboratory experiments of Soltanpour and Samsami (2011) confirms the accuracy of the numerical model. Figure (1) shows the variation of damping rate with surface wave frequency for various values of mud shear modulus.…”
Section: Resultssupporting
confidence: 64%
“…First, the damping expression (34) assumes a 1/ dependence between the elastic and viscous responses of the sediment, and combines both dissipation mechanisms into one single term. In contrast, experimental studies [39,[45][46][47][48][49] that have reported both the shear and the viscous properties (flow curves) of sediments do not suggest a straightforward 1/ dependence between the two. The elastic and the viscous responses may vary individually, depending on the strain amplitude and/or frequency ranges (in for example, shear viscosity [58,59] and elastic modulus [61]).…”
Section: Linear Expressions Of Anderson and Hampton (1980)mentioning
confidence: 87%
“…The elastic and the viscous responses may vary individually, depending on the strain amplitude and/or frequency ranges (in for example, shear viscosity [58,59] and elastic modulus [61]). These may furthermore depend on the salinity, the mineralogical composition and the concentration [46,48]. Second, there exists a discrepancy because of the use of Re( * ) in the resonance frequency expression (35) and Im( * ) in the damping coefficient (34).…”
Section: Linear Expressions Of Anderson and Hampton (1980)mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, nonlinear models have the capability of being extended from small amplitude wave to nonlinear wave, which may enhance or reduce surface energy dissipation. Enhanced or reduced damping rates are observed in the literature using different wave heights of constant wave frequency [e.g., Nagai et al, 1984;Sakakiyama and Bijker, 1989;Liu et al, 2011;Soltanpour and Samsami, 2011]. One of the overarching goals of studying wave-mud interactions is to be able to inversely estimate the properties of muddy seabeds, such as the mud layer thickness, viscosity, and density [Rogers and Holland, 2009;Sheremet et al, 2011;Tahvildari and Kaihatu, 2011].…”
Section: Introductionmentioning
confidence: 99%